Gojek Indonesia's Responsibility to Consumers Using Online Transportation Services - Merry Roseline Pasaribu; Roswita Sitompul; Sri Sulistyawaty; Kartina Pakpahan (Budapest International Research and Critics University, 2023)
Each country strives to achieve what is the goal of the Nation and State which for Indonesia is stated in the 4th paragraph of the 1945 Constitution, namely to achieve public welfare, one way is to improve transportation facilities, this is very important to support the activities of the daily community. . This research is socio-juridical, looking at how an existing legal regulation is applied in society. Data collection was carried out by means of observation, interviews and questionnaires consisting of online motorcycle taxi drivers and office staff of online motorcycle taxi institutions and consumers.From the results of the research that the legal relationship between online motorcycle taxi drivers is only a partnership relationship and also as a liaison between partners and consumers, however the partnership relationship is made with a separate role and it is written that the partner frees PT Paket Global Semesta in criminal and civil lawsuits, because each agreement it must comply with Article 1320. Based on the provisions of the law that online motorcycle taxi drivers are not appropriate as partners because this is only an individual and in the standard agreement entered into by PT. Paket Global Semesta which regulates the rights and obligations of both parties, in fact it provides more benefits than the producer and as if the entrepreneur is transferring the risk to the partner, this is still a dilemma about the legal consequences that will occur in the implementation of all activities offered by producers to consumers, there are still many discrepancies.